Symbolic and ritual enactments of nationalism – a visual study of Jobbik's gatherings during Hungarian national day commemorations. Issue 3 (3rd July 2017) - Hyttinen, Anniina; Näre, Lena
Abstract : This article analyses the symbolic and ritualistic enactments of contemporary Hungarian nationalism during national day commemorations organised by the extreme right-wing party Jobbik. Drawing on three ethnographic field trips to Budapest, Hungary, during national day celebrations in 2013–2014 illustrated by nine photos taken by the first author, the article analyses the manifestations of nationalism through the use of various visual symbols, slogans and ritualistic elements such as marching and singing. Jobbik's gatherings have a rich repertoire of symbolic and ritualistic elements, which primarily communicate Hungary's mythical heroic past and revisionism that is connected to xenophobic and anti-Semitic mentality. The article argues that while these modern rituals can be located somewhere between the 'banal' and 'hot' nationalism, they maintain the ability to mobilise people by evoking collective memory. Jobbik is able to utilise the strong emotional potential condensed in the symbols through ritual enactment, which creates Durkheimian solidarity among the participants and emphasises oneness. However, such a sense of solidarity is based on exclusion and on the division into 'us' and 'them', rather than inclusion. The discussion is supported with photographic data from the gatherings.